Entomological indices of Anopheles gambiae sensu lato at a rural community in south-west Nigeria (2009)
Background & objectives: Investigations were conducted to obtain key entomological indices of Anopheles gambiae s.l. at Igbo-Ora, a rural community in south-west Nigeria. Methods: Mosquitoes were caught daily for a week from rooms where tenants had slept the previous night in each of the four months June, July (2001), and August, September (2002). Anopheles gambiae s.l. sibling species were PCR-identified, the blood meal origin was determined by direct ELISA, and the circumsporozoite antigen by sandwich ELISA. Mean weekly rates were calculated. Results: The mean human biting rates were 0.90 and 1.6 in 2001 and 2002 respectively. The mean weekly anthropophilic rates for An. gambiae s.l. were 82 and 86% in 2001 and 2002 respectively; they were high in An. gambiae s.s., An. arabiensis and non-identified species in the complex. The mean weekly circumsporozoite rates were 6.70% in 2001 and 6.30% in 2002. The mean weekly entomological inoculation rates (EIR) were 4.95 and 5.05 in 2001 and 2002 respectively; the seasonal (6-month) rates were high: 128.7 in 2001 and 131.3 in 2002, compared to data from other rural communities on the continent. Interpretation & conclusion: The implications of these findings on the role of An. gambiae s.l. in the holoendemicity of malaria at Igbo-Ora are discussed.